TRIGONOMETRY ON THE GALILEO PLANE (Scientific journal of the Fergana State University, 2025)
This article discusses the properties of trigonometry on the Galilean plane or parabolic trigonometry, which is similar to the properties of trigonometry on the Euclidean plane. When defining trigonometric functions, the relationship between angles and functions is proven using theorems and statements.